2007 14th IEEE International Conference on Electronics, Circuits and Systems 2007
DOI: 10.1109/icecs.2007.4511179
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Capacitive-Feedback Differencing Amplifier for Temporal Contrast IR Sensors

Abstract: This paper presents a small-area, ultra low-power, low-mismatch differencing amplifier for use in transient pixels of micro-bolometer based temporal contrast IR sensors. The two-stage capacitive-feedback amplifier works in the sub-threshold domain, has a voltage gain of 46dB, a 3dB bandwidth of about 10kHz and consumes 85nW of static power. The amplifier circuit has been fabricated in a 0.35µm standard CMOS process and consumes less than 2000µm 2 of silicon area, enabling a square pixel size of 50µm×50µm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The problems with charge injection in our cDVS pixel arise mostly from the flawed reset circuit. Although Posch et al have demonstrated that a two-stage architecture can provide high gain [28], we concluded for our circuit that two-stage switched capacitor amplifiers are not suitable, and therefore we have proposed circuit improvements which only use a single switched-capacitor amplifier stage.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The problems with charge injection in our cDVS pixel arise mostly from the flawed reset circuit. Although Posch et al have demonstrated that a two-stage architecture can provide high gain [28], we concluded for our circuit that two-stage switched capacitor amplifiers are not suitable, and therefore we have proposed circuit improvements which only use a single switched-capacitor amplifier stage.…”
Section: Discussionmentioning
confidence: 66%
“…SPICE simulations of the pixel before (and after) fabrication do not show this large injection effect, because in the simulations, the charge injected onto the input of from and from opening compensate. An easy fix to this problem is to split the generation of the two reset signals, as described in Section V and as used in the sDVS [34], or to use a circuit similar to the one used by Posch et al [28].…”
Section: Measurement Resultsmentioning
confidence: 99%
See 3 more Smart Citations